Identificação e isolamento de microrganismos envolvidos na fermentação de kefir de leite - Frenzel, Natalia Becker (2020)
Foods that are present in fermentation process show changes in their characteristics, such as changes in flavor, aroma and texture, which attract the attention of several consumers, in addition to being associated with health benefits. Kefir is a drink originated from the fermentation of milk from a complex mixture of bacteria and yeasts that live symbiotically and form the kefir grain. The identification and characterization of the microbiota present in the kefir grain can enable production on a larger scale, since knowledge of it can stimulate the production of starter cultures, which can contribute to obtaining a stable, standardized and safe drink. In this context, the objective of this work was to evaluate the microbiota belonging to the kefir grains as well as to identify and isolate the microorganisms belonging to the kefir drink, aiming at the identification of possible candidates for the preparation of starter culture. The sequencing of the V4 region of the 16S rRNA gene from the DNA extracted from the kefir grains was carried out to characterize the bacterial community. In parallel, the cultivation and isolation of the microorganisms present in the grains and in the kefir drink was carried out, aiming at obtaining isolated representatives of the groups of lactic bacteria, acetic bacteria and yeasts, followed by the morphological and biochemical characterization and molecular identification. Cell viability and identification of the microorganisms present in the kefir drink were estimated by plating and counting the colony-forming units in media for isolation of acetic bacteria, lactic bacteria and fungi. Through the analysis of grain sequencing, the genus predominantly found was Lactobacillus, followed by Lactococcus, Acetobacter, Faecalibacterium, Leuconostoc, Bacteroides and Bifidobacterium. No isolates were obtained from the kefir grain, however, 26 isolates were recovered from the drink. Through gram staining, of the total isolates, 6 showed characteristics of Gram positive bacteria, 6 of Gram negative bacteria and 14 of yeast. By sequencing the 16S rRNA genes, one isolate was identified as Lactococcus lactis and the other as Bacillus thuringiensis. By sequencing the ITS region, an isolate was identified as Candida parapsilosis. The three species mentioned have already been described in the literature as being found in the kefir drink, but still do not represent the microbial diversity found in the kefir grain. In this sense, alternative isolation techniques need to be evaluated and tested, in order to expand access to the isolates present in the kefir grain with a focus on the formulation of a starter culture.